Understanding Is Embedded in History (KULT_online, 2009)
In the study Siam und Europa Sven Trakulhun examines travelogues about Siam (modern-day Thailand) from the 16th and 17th centuries. Instead of writing classical reception history, Trakulhun takes into account Thai history and historiography with the aim of contributing to the field of comparative history. He begins by introducing the relevant historical backgrounds for both Europe and Siam, relying in part on individual, non-European sources. In addition to recording the conditions and contexts of intercultural encounters, the author describes how the extant lore regarding Siam became established stereotypes when, beginning in the 18th century, Siam isolated itself from Europe. Yet Trakulhun notes that even before this shift, there was already a tendency for Siam to seem stranger to Europeans the more they learned about the country. The author acknowledges that it is impossible to write a completely unbiased entangled history, but emphasises the importance of continuing in this line of study.